Relationship between the sensitization to shrimp and mites. Exploration of cross-reactivity due tropomyosin - Karen Estefania Hernández-Moreno; María Muñoz; Víctor Calvo; Libia Susana Diez-Zuluaga; Jorge Sánchez (Revista Alergia México, 2019)
Background: Little is known about the sensitization to shrimp in patients with respiratory allergies who are sensitized to mites and about the clinical relevance of that sensitization in the tropical region.